2002
DOI: 10.1007/s12043-002-0213-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pr-Ca substitution on the transport and magnetic behavior of LaMnO3 perovskite

Abstract: The effect of simultaneous substitution of a fluctuating cation and a divalent cation in LaMnO 3 perovskite modifies the properties of the material to exhibit large valence colossal magnetoresistance (CMR) effect. A good example of these properties is (La 1−2x Pr x Ca x )MnO 3 (LPCMO) type CMR material. In this communication it is reported that, with the increase in x (for x = 0.1, 0.15, 0.2), the T c varies between 100 and 120 K with improvisation in metal-insulator transition. Interestingly, resistance incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…All the samples exhibit metal to insulator transition at T P , which increases with Ba-content (as indicated in the small brackets in figure 3). Thaker et al [25] have reported the transition temperature ∼135 K for LPCMO sample, which increases upon the substitution of Ba 2+ at Ca 2+ site, as observed for the present case of LPCBMO system. Also, with applied magnetic field, T P shifts towards higher temperature.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…All the samples exhibit metal to insulator transition at T P , which increases with Ba-content (as indicated in the small brackets in figure 3). Thaker et al [25] have reported the transition temperature ∼135 K for LPCMO sample, which increases upon the substitution of Ba 2+ at Ca 2+ site, as observed for the present case of LPCBMO system. Also, with applied magnetic field, T P shifts towards higher temperature.…”
Section: Resultssupporting
confidence: 83%
“…62)). The similar distorted orthorhombic structure was reported for LPCMO (x = 0.00) compound [25,26]. Samples possess orthorhombic unit cell, where with the increase in Bacontent (x), lattice parameters and cell volume increase.…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations